Earth Stewardship of rangelands: coping with ecological, economic, and political marginality. Issue 7 (1st September 2013) - Sayre, Nathan F; McAllister, Ryan RJ; Bestelmeyer, Brandon T; Moritz, Mark; Turner, Matthew D
Abstract : Rangelands encompass 30–40% of Earth's land surface and support 1 to 2 billion people. Their predominant use is extensive livestock production by pastoralists and ranchers. But rangelands are characterized by ecological, economic, and political marginality, and higher value, more intensive land uses are impinging on rangelands around the world. Earth Stewardship of rangelands must address both livestock management and the broader socioecological dynamics that promote land‐use changes, fragmentation, and degradation. We identify specific gradients on which human–rangeland systems can be arrayed, including issues of variability, adaptation to disturbance, commercialization, land‐use change, land‐tenure security, and effective governance, and we illustrate the gradients' interactions and effects in sites worldwide. The result is a synthetic framework to help in understanding how rangeland Earth Stewardship can be achieved in the face of marginality, globalization, and climate change.